PELESTARIAN KESENIAN RANDAI OLEH GROUP MANGGIH MUDO DI KELURAHAN MANGGIS GANTING KECAMATAN MANDI ANGIN KOTO SELAYAN KOTA BUKITTINGGI - Vika Arifiani; Marzam Marzam; Syahrel Syahrel (SENDRATASIK UNP, 2017)
This article aimed to describe the preservation of the art by Manggih Mudo Group in Manggis Ganting Sub-District, Mandiangin District / Koto Selayan, Bukittinggi which is still used and exists in Bukittinggi. This was a qualitative research which used descriptive method. The data collection was done by doing observation, interview, and literature study. The object of this research was Randai that was in Manggih Mudo Group, Manggis Ganting Sub-district, Bukittinggi. The results of this research showed that Manggih Mudo Group performed the preservation of Randai by inviting the government to participate in the preservation of Randai in Manggis Gantiang Sub-district. The city government provided financial support to Manggih Mudo Group as a contribution to the preservation of Randai. The government also involved Manggih Mudo Group in the events or the activities held by the government. For example, in 2015, the government invited the Manggih Mudo Group in the art exhibition held in RRI building. Then Manggih Mudo Group was also invited in Semarak Lima event held at the Jam Gadang festival. Manggih Mudo Group also performed the preservation by inheriting Randai to younger generations; it provided routine exercises done around the Mr. Yazirwan’s house, which aimed to introduce Randai to the younger generations. Maintaining the existence of Manggih Mudo Group was also an effort to preserve Randai. Randai was actively performed either in Manggis Ganting Sub-district or outside Manggis Ganting Sub-district. For example, it was performed in wedding receptions and to welcome guests from a company. Keywords: Conservation, equality, Group Encounter